Local gyrification index in patients with major depressive disorder and its association with tryptophan hydroxylase‐2 (TPH2) polymorphism. Issue 3 (3rd November 2016) - Han, Kyu‐Man; Won, Eunsoo; Kang, June; Kim, Aram; Yoon, Ho‐Kyoung; Chang, Hun Soo; Son, Kyu Ri; Lee, Min‐Soo; Tae, Woo‐Suk; Ham, Byung‐Joo
Abstract: The tryptophan hydroxylase‐2 ( TPH2 ) gene is considered a promising genetic candidate regarding its association with a predisposition to major depressive disorder (MDD). Local gyrification reflects the early neural development of cortical connectivity, and is regarded as a potential neural endophenotype in psychiatric disorders. They aimed to investigate the alterations in the cortical gyrification of the prefrontal cortex and anterior cingulate cortex and their association with the TPH2 rs4570625 polymorphism in patients with MDD. One hundred and thirteen patients with MDD and eighty‐six healthy controls underwent T1‐weighted structural magnetic resonance imaging and genotyping for TPH2 rs4570625. The local gyrification index of 22 cortical regions in the prefrontal cortex and anterior cingulate cortex was analyzed using the FreeSurfer. The patients with MDD showed significant hypergyria in the right rostral anterior cingulate cortex ( P = 0.001), medial orbitofrontal cortex ( P = 0.003), and frontal pole ( P = 0.001). There was a significant genotype‐by‐diagnosis interaction for the local gyrification index in the right rostral anterior cingulate cortex ( P = 0.003). Their study revealed significant hypergyria of the anterior cingulate cortex and prefrontal cortex and an interactive effect between the diagnosis of MDD and the genotype in the anterior cingulate cortex. This might be associated with the dysfunction of neural circuits mediating emotion processing, which could contribute to pathophysiology of MDD. Hum Brain Mapp 38:1299–1310, 2017 . © 2016 Wiley Periodicals, Inc.